French-speaking theses and linguistic plurality in African schools - (:unkn) unknown (My University, 2023)
Many French-speaking PhD and thesis deal with school systems in Africa and language teaching in a plurilingual context. The most numerous concern the teaching of and in French, most often studied both as a language of instruction and as a second language. Alongside the theses with a didactic orientation, the most numerous, we see more and more theses positing linguistic plurality at school as a social and political question. Two geographical groups stand out, the Maghreb and sub-Saharan Africa. It is in the Maghreb that the theses defended between 2000 and 2020 are the most numerous. There, multilingualism includes Berber-speaking populations. In sub-Saharan Africa the diversity of languages is greater on this scale Here, alongside the didactics of French, native and national languages are also the subject of theses with a didactic orientation.
Keywords: African Research